Budi Sejahtera, Reliance and Resilient at Mak Teh Enterprise - Yahya, Rohaziah; Ismail, Yusof; Mhd. Sarif, Suhaimi (IIUM Journal of Case Studies in Management, 2023)
Mak Teh Enterprise showcases the incorporation of budi sejahtera, reliance and resilience in a 15-year old grocery shop. The primary intention was to serve the community with the budi sejahtera through a simple grocery shop. The support from the family and community is vital and has made Mak Teh Enterprise survive. There is no reason for any commercial entity to incorporate budi sejahtera or charitable intention into the business. Keywords: Budi sejahtera, Small business, Resilience.